The Effect of Customer's Level of Understanding on the Purchase of Sharia Education Insurance Products (Case Study at PT. Asurasi Jiwa Syariah Bumiputera KPS Medan) - Dahlianti, Hervina; Imsar; Jannah, Nurul (Ikatan Da'i Indonesia, 2023)
Sharia Education Insurance is a type of insurance that provides protection against the needs of children's education costs. This study aims to determine the effect of the level of customer understanding on the purchase of Islamic education insurance products. This study uses primary data generated from respondents' questionnaire data. The population in this study are customers who use Islamic education insurance products, the sample is taken using the sample probability technique with a total of 95 respondents obtained using the slovin formula. The data analysis used in this research is the data instrument test, classical assumption test, simple linear regression analysis, and t test. The results of this study indicate that the variable of customer understanding (independent variable) with the results of tcount 6.134 > ttable 0.202, and a significance value of 0.003 <0.005. So it can be concluded that the customer understanding variable (independent variable) has a positive and significant effect on the purchase of Islamic education insurance products (the dependent variable) with an influence level of 28.8% which is included in the moderate relationship level, this is caused by the existence of factors that affect customers.